Pengaruh Kualitas Pelayanan, Lokasi dan Citra Rumah Sakit Terhadap Keputusan Berkunjung Pasien Di RSUD Ngimbang Lamongan - Setiya Wati, Intan; Moh Agung Surianto (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
This study aims to identify the influence of service quality variables, location and hospital image on the decision to visit patients at Ngimbang Regional Hospital. This research used quantitative research involving 160 patients from the relevant regional hospitals. The analysis technique used is multiple linear analysis with the help of SPSS version 26, the data sources used come from primary and secondary data. The results of the analysis show that the variables of service quality and location influence the decision to visit patients at Ngimbang Lamongan Regional Hospital. Meanwhile, the hospital image variable has no influence on the decision to visit patients at Ngimbang Lamongan Regional Hospital. This research has limitations because it was only conducted at Ngimbang Lamongan Regional Hospital.